Peran Pendidikan IPS dalam Pendidikan Multikultural - Putu Ronny Angga Mahendra (Journal on Education, 2023)
This research is a type of descriptive research with the method of literature review or literature study. Collecting data with documentation about the role of social studies education in multicultural education in Indonesia. Indonesia has a diverse society, ranging from culture, beliefs, ethnicity and others. Problems in this country certainly have an impact on social life. Social science education plays a role in promoting a peaceful life, encouraging one to improve adaptation to one another, can promote better communication and improve one's relationships. Social science education integrates various disciplines such as geography, history, sociology, economics and social anthropology. The implementation of social studies learning is emphasized in the field of education, so as to gain additional knowledge about attitudes and behavior, values, and good manners and can play a role in people's lives and can instill scientific attitudes in order to solve problems faced around them. Multicultural education as a strategy to utilize the various cultures of different student societies is the uniqueness or characteristic of students to form a multicultural attitude of mutual understanding and respect so as to create a tolerant education sector. The integration of educational social studies studies in multicultural education can contribute to realizing a resilient society in the development of globalization and upholding the basic philosophy stating that diversity makes education more quality and more advanced.